Religiosidade em indivíduos hipertensos de uma unidade do programa saúde da família de Pedras de Fogo PB - Pereira, Valdelene Nunes de Andrade (2013)
The purpose of this study was to analyze the influence of religiosity in 139 patients between 25 and 75 years old which being treated for arterial hypertension in a family health program located in the city of Pedras de Fogo, Paraíba, in the period between December, 2011 and December, 2012. The sample included two groups: the Study Group, with 73 people that accepted to be part of the research, in which the religious activities were intensified; and the Control Group, with 66 patients that did not have any religion or did not accept the intensification of their religious activities. All of them had signed an informed consent for participation in the study and the clinical medical routine in both groups was maintained. It was applied: a clinical social-demographic questionnaire with a personal profile and the Scale Religious Attitude (Aquino, 2005) at the start and end of the nine months period. The analysis of the data was made in the program Statistical Package for the Social Sciences, version 18. Although there have been no significant reductions in the blood pressure in the subjects of the research, there was in the Study Group a decrease in the use of sedatives and antidepressants. Correlating some complaints that was reduced in a percentage in the Study Group with the intensification of religious activities, it was observed that: there is an inverse proportional relationship between prayer and chest pain (r = -0,259; p < 0,01), fear of death (r = -0,189; p < 0,05), and cold hands (r = -0,195; p < 0,05). Bad feelings (r = -0,235; p < 0,01) occurred less in the patients that took the communion and the recitation of the Rosary may have contributed to reduce dizziness (r = -0,217; p < 0,05). It was also observed a direct correlation between forgiveness and humor among the people who were the most religious of the sample (r = 0,233; p < 0,05) in the first step of the study. The evaluation of the reports points out mutual religiosity as a fator that improves the doctor-patient relationship. We have concluded that religiosity benefits people health in general, strengthening the trust of the patient in the doctor, and can be used as a therapeutic tool also in the field of mental health.